The Effect of Price, Promotion, and Location Perception on The Purchase Decision of Indonesian Iced Tea Fatmawati Branch, Kedungmundu - Safitri, Rida Amalia; Haerudin, Haerudin; Jumai, Jumai; Nurhayati, Nurhayati (Economics and Business International Conference Proceeding, 2024)
Es Teh Indonesia is one of the well-known franchise beverage businesses in Indonesia, with more than 800 branch outlets spread throughout Indonesia. This study aims to find out how the Influence of Price Perception, Promotion, and Location on the Purchase Decision of Indonesian Ice Tea Fatmawati Branch, Kedungmundu. The research uses quantitative methods. The population in this study is customers of Es Teh Indonesia Fatmawati Branch, Kedungmundu. The sample used was as many as 100 respondents using the purposive sampling technique. The analysis tool used is multiple linear regression analysis. The results of this study show that it is partially known that the variables of Price Perception and Promotion have a positive and significant effect on the Purchase Decision at Es Teh Indonesia Fatmawati Branch, Kedungmundu, while Location does not have a significant effect on the Purchase Decision of Es Teh Indonesia Fatmawati Branch. Furthermore, simultaneously Price Perception, Promotion, and Location have a significant effect on the Purchase Decision of Indonesian Ice Tea Fatmawati Branch, Kedungmundu.